Evaluation of Worker Fatigue During Exoskeleton-Assisted Tasks with Varying Intensities - Daehwi Jo; Gu Young Cho; Kyung-In Kang; Hyunsoo Kim (Buildings)
Worker fatigue is a significant concern in construction environments, particularly for high-intensity repetitive tasks that contribute to physical strain and increase the risk of accidents. This study evaluates the impact of exoskeleton-assisted work on fatigue reduction across different construction tasks and intensity levels. Using inertial measurement unit (IMU) sensors and the dynamic time warping (DTW) algorithm, we quantitatively analyzed movement patterns and fatigue accumulation in workers performing carrying, scaffold installation, and masonry tasks under both low-intensity and high-intensity conditions. The results demonstrate that exoskeleton support effectively reduces DTW values, indicating improved movement consistency and lower fatigue levels. Specifically, DTW values were reduced by approximately 15–25% with exoskeleton use, with the most significant reductions observed in scaffold installation (25%) and carrying tasks (22%). Time-series analysis further revealed that exoskeletons not only decrease overall fatigue accumulation but also slow the rate of fatigue increase, extending the period in which workers can maintain safe and efficient movement patterns. The findings highlight the potential of exoskeleton technology to enhance worker safety and reduce fatigue-related risks in physically demanding construction tasks. This study contributes to the advancement of objective fatigue assessment methodologies and provides insights into the practical implementation of exoskeletons in construction environments. However, this study is limited by its short-term design, task scope, and the absence of long-term fatigue tracking, which will be addressed in future work.